After the Fall: How Perceived Self-Control Protects the Legitimacy of Higher-Ranking Employees After Status Loss - Carson Marr, Jennifer; Pettit, Nathan; Thau, Stefan (Organization Science, 2019)
We investigate how higher-ranking organizational members can protect their legitimacy after status loss. We theorize that after status loss, internal stakeholders will scrutinize the behavior of higher-ranking members to determine whether they are still deserving of their high-ranking position (i.e., legitimate) and that those members who display self-control (e.g., persistence, poise, restraint) after status loss signal legitimacy to scrutinizing internal stakeholders. In a laboratory experiment (Study 1), we found that leaders who displayed higher (versus lower) self-control after status loss were judged as more legitimate and were less likely to be challenged. This effect of higher perceived self-control on legitimacy and challenging behavior after status loss was explained by positively influencing internal stakeholders’ instrumental and moral evaluations of the higher-ranking individual. In an online experiment with working adults (Study 2), we constructively replicated these results and found that high self-control is more important for positive legitimacy judgments after status loss than when no status loss has occurred. Finally, in a critical incident study (Study 3), we explored whether the type of perceived self-control influenced the efficacy of the self-control strategy. We found that self-presentation was the most effective “type” of self-control display after status loss, and displaying self-control in multiple ways (e.g., task-related and self-presentation) increased the efficacy of perceived self-control. We discuss the implications of this research for legitimacy judgments, status loss, and self-control.